2017
DOI: 10.1021/acs.jmedchem.6b01801
|View full text |Cite
|
Sign up to set email alerts
|

Design and Elaboration of a Tractable Tricyclic Scaffold To Synthesize Druglike Inhibitors of Dipeptidyl Peptidase-4 (DPP-4), Antagonists of the C–C Chemokine Receptor Type 5 (CCR5), and Highly Potent and Selective Phosphoinositol-3 Kinase δ (PI3Kδ) Inhibitors

Abstract: A novel molecular scaffold has been synthesized, and its incorporation into new analogues of biologically active molecules across multiple target classes will be discussed. In these studies, we have shown use of the tricyclic scaffold to synthesize potent inhibitors of the serine peptidase DPP-4, antagonists of the CCR5 receptor, and highly potent and selective PI3K δ isoform inhibitors. We also describe the predicted physicochemical properties of the resulting inhibitors and conclude that the tractable molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…At the hA 2A AR and hA 2B AR, 46a caused a small but significant rightward shift of the NECA concentration response curve only at the highest concentration tested (1 μM) (Figure S9), with no detectable effect at the hA 3 AR. Therefore, the estimated affinity of 46a for each of the adenosine receptor subtypes, quantified using the Gaddum equation as previously described, was relatively low (p K D hA 2A AR = 6.11 ± 0.08, p K D hA 2B AR = 6.16 ± 0.07, p K D hA 3 AR <6, n = 3) , compared to that observed from the NanoBRET assay (Figure and Table ). Therefore, the small BRET signal detected with 46a in HEK293 cells expressing NanoLuc-hA 2A AR and NanoLuc-hA 2B AR may reflect BRET between 46a bound to endogenous hA 1 ARs and the transfected NanoLuc-tagged A 2 AR receptors as a result of oligomerization.…”
Section: Resultsmentioning
confidence: 73%
“…At the hA 2A AR and hA 2B AR, 46a caused a small but significant rightward shift of the NECA concentration response curve only at the highest concentration tested (1 μM) (Figure S9), with no detectable effect at the hA 3 AR. Therefore, the estimated affinity of 46a for each of the adenosine receptor subtypes, quantified using the Gaddum equation as previously described, was relatively low (p K D hA 2A AR = 6.11 ± 0.08, p K D hA 2B AR = 6.16 ± 0.07, p K D hA 3 AR <6, n = 3) , compared to that observed from the NanoBRET assay (Figure and Table ). Therefore, the small BRET signal detected with 46a in HEK293 cells expressing NanoLuc-hA 2A AR and NanoLuc-hA 2B AR may reflect BRET between 46a bound to endogenous hA 1 ARs and the transfected NanoLuc-tagged A 2 AR receptors as a result of oligomerization.…”
Section: Resultsmentioning
confidence: 73%
“…Dalton et al [113] describe the development of a covalent PI3Kδ inhibitor ( 34 ) that achieves its isoform selectivity via the tryptophan shelf, and covalently interacts with the conserved lysine, δLys779 (PDB ID 6EYZ) (Figure 6c). Schwehm et al [114] have reported the design of a novel tricyclic scaffold ( 35 ) which can be used as a tryptophan shelf binding motif (Figure 6c). Clinical candidates GSK2269557 ( 36 ) and GSK2292767 ( 37 ) both use the tryptophan shelf (PDB ID 5AE8, 5AE9) (Figure 6c) [73], as do a series of pyrazolopyridines described by Hamajima et al ( 38 , Figure 6c) [115].…”
Section: Structural Determinants Of Isoform Selectivitymentioning
confidence: 99%
“…Mechanistically, CCR5 forms a co-receptor with the viral envelope glycoprotein gp120, which is required for HIV-1 cell recognition and entry leading to infection. 237,238 Maraviroc ( 162 ) is a marketed allosteric drug for anti-HIV (Figure 23), stabilizing CCR5 in an inactive conformation that blocks CCR5-gp120 interaction by allosterically binding to CCR5. 239,240 The cocrystal complex of CCR5 and maraviroc demonstrate that maraviroc occupies an extracellular site of the 7TM helical bundle.…”
Section: Recent Advances In the Discovery And Design Of Class A Gpcr mentioning
confidence: 99%